Improving Security of Blockchain Through Authorisation - Sharma, Vivek; Kumar, Nagendra (International Journal of Computer Sciences and Engineering, 2025)
Blockchain is the chain of blocks and each block consists a time stamp, transaction data and a cryptographic hash of previous block. It is a decentralized distributed network in which each peer node connected with each other and shares history of all the transactions. Each new block added to blockchain whenever a transaction occur need to be verified by all the peer node and transaction executed successfully if more that 50% allows. There are some vulnerabilities which are present in Blockchain because of its publicly open network and lack of security certification. We tried to modify the Blockchain with the use of smart contracts with the existing blockchain network and using X.509 Certification for specifying the permission allotted to each peer node at the time it is added to the network.